Pengaruh belanja modal dan investasi terhadap pertumbuhan ekonomi melalui kesempatan kerja di Provinsi Jambi - Zamzami, Wahyu; Junaidi, Junaidi; Hari Prihanto, Purwaka (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
The purpose of this study is to analyze: 1) the direct effect of capital expenditure and investment on the employment opportunities of Jambi Province in the period 2000-2018; 2) the direct effect of capital expenditure, investment and employment opportunities on the economic growth of Jambi Province in the period 2000-2018; and 3) the indirect effect of capital expenditure and investment on economic growth through employment opportunities in the Jamni Province period 2000-2018. The dataÂ analysis method used is path analysis. Based on the results of the analysis it is known that: 1) simultaneous capital expenditure and investment have a significant effect on employment opportunities in Jambi Province during the period 2000-2018, while partially the variables that significantly influence employment opportunities in Jambi Province are investment variables. 2) simultaneously capital expenditure, investment and employment have a significant effect on the economic growth of Jambi Province during the period 2000-2018, while partially the variables that significantly influence the economic growth of Jambi Province are investment and employment opportunities variables. 3) investment has an indirect effect on economic growth in Jambi Province, while capital expenditure does not have an indirect effect on economic growth in Jambi Province.